Epidemiology 2021
DOI: 10.1183/13993003.congress-2021.pa1726
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Multidrug Resistant Tuberculosis among TB Patients in Malaysia

Abstract: Background: Currently multidrug-resistant tuberculosis (MDR-TB) poses a signi cant public health concern in Malaysia.Objective: This study is aimed to evaluate the prevalence of MDR-TB in Malaysian tuberculosis patients. Method. A retrospective analysis was performed, and data was obtained from the Malaysian National TB Information System (TBIS) between 2009 and 2019. A record of 989 MDR-TB cases were identi ed and associated risk characteristics such as marital status, gender, ethnicity, employment status, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…10% of them meet the criteria for extensively drug-resistant with additional resistance to any fluoroquinolone, and to at least one injectable second-line drug (capreomycin, kanamycin or amikacin) [25] [26]. Malaysian National TB Information System (TBIS) between 2009 and 2019 reported that the incidence of MDR-TB among patients with TB infections in Malaysia was 0.34% [27]. Therefore, public education on prevention, early diagnosis, and treatment with good drug compliance is essential to avoid these disastrous complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…10% of them meet the criteria for extensively drug-resistant with additional resistance to any fluoroquinolone, and to at least one injectable second-line drug (capreomycin, kanamycin or amikacin) [25] [26]. Malaysian National TB Information System (TBIS) between 2009 and 2019 reported that the incidence of MDR-TB among patients with TB infections in Malaysia was 0.34% [27]. Therefore, public education on prevention, early diagnosis, and treatment with good drug compliance is essential to avoid these disastrous complications and mortality.…”
Section: Discussionmentioning
confidence: 99%